Integrated experimental and numerical study of a bubble column bioreactor with immobilized S. cerevisiae for ethanol production in non-Newtonian fermentation broth - Abutu, David; Aderemi, Benjamin O.; Ameh, Alewo O.; Wan Mohd Hafizuddin, Wan Yussof; Yerimae, Emmanuel A.; Agi, Augustine Aja (Taylor & Francis, 2026)
The design and scale-up of bubble column bioreactors (BCBs) for ethanol fermentation are constrained by non-Newtonian fluid behavior and mass transfer limitations, particularly when immobilized cells are employed. This study integrates experimental and numerical approaches to evaluate ethanol production using Saccharomyces cerevisiae immobilized in calcium alginate beads within a 500 mL lab-scale BCB. A multiscale simulation framework was developed, combining Monod kinetics (SciPy), glucose diffusion in spherical beads (FiPy), and shear-thinning hydrodynamics using a power-law model (FEniCS, n = 0.55). Model predictions were calibrated with triplicate batch fermentations over 48 h, achieving strong agreement between simulations and experiments (R2 > 0.93; RMSE < 1.0 g/L). The experimental ethanol yield was 0.44 g/g glucose (8.8 +- 0.3 g/L ethanol), closely matching the simulated value of 0.45 g/g. Diffusion modeling revealed substrate depletion in bead cores, explaining the ethanol plateau observed experimentally, as internal glucose dropped below 0.2 g/L despite bulk concentrations >1.0 g/L at 24 h. Predictive simulations indicated that reducing bead diameter from 4 mm to 2 mm improved core glucose availability (0.1 → 0.8 g/L at 24 h) and increased yield from 0.45 to 0.52 g/g. Scale-up simulations from 500 mL to 2 L predicted higher circulation velocity (0.012 → 0.025 m/s), but stagnant zones increased disproportionately (8% → 15% reactor volume) due to shear-thinning effects. These results demonstrate the value of integrating experimental data with multiscale modeling to enable mechanistic interpretation, predictive scenario testing, and rational scale-up of immobilized-cell BCBs under non-Newtonian conditions.